2023
DOI: 10.3389/fendo.2023.1144323
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin ameliorates inflammation, oxidative stress, and reproductive outcomes in endometriosis patients undergoing assisted reproduction: A randomized, triple-blind placebo-controlled clinical trial

Abstract: PurposeIn a randomized, triple-blind, placebo-controlled clinical trial (RCT) including 50 infertile women with endometriosis candidate for assisted reproductive techniques (ART), we studied the effect of Astaxanthin (AST) on pro-inflammatory cytokines, oxidative stress (OS) markers, and early pregnancy outcomes.MethodsBefore and after 12 weeks of AST treatment (6 mg per day), blood serum and follicular fluid (FF) samples were collected from 50 infertile women with endometriosis stage III/IV undergoing ART. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It has been reported that the use of synthetic progestins prior to in vitro fertilization and embryo transfer has no significant benefit on clinical outcomes in endometriosis-associated infertility [ 21 ]. A recent study suggests that astaxanthin, with its anti-inflammatory and antioxidant properties, may be a reliable intervention for the prevention of endometriosis-related infertility [ 22 ]. Endometriosis-associated infertility already causes physical and psychological distress and suffering for both patients and their partners [ 23 , 24 ], and understanding its long-term disease burden will help to increase the importance of preventing endometriosis from the beginning and managing endometriosis-associated infertility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the use of synthetic progestins prior to in vitro fertilization and embryo transfer has no significant benefit on clinical outcomes in endometriosis-associated infertility [ 21 ]. A recent study suggests that astaxanthin, with its anti-inflammatory and antioxidant properties, may be a reliable intervention for the prevention of endometriosis-related infertility [ 22 ]. Endometriosis-associated infertility already causes physical and psychological distress and suffering for both patients and their partners [ 23 , 24 ], and understanding its long-term disease burden will help to increase the importance of preventing endometriosis from the beginning and managing endometriosis-associated infertility.…”
Section: Discussionmentioning
confidence: 99%
“…The follicular uid was collected concurrently with oocyte retrieval [23]. Brie y, transvaginal ultrasoundguided oocyte retrieval was conducted 36-37 hours following hCG injection, coinciding with the collection of follicular uid.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Astaxanthin (AST) is a natural lipid-soluble and red–orange xanthophyll carotenoid widely found in marine seafood, such as shrimp, lobster, and crab, especially in their shell portions, and in several microorganisms, such as Phaffia rhodozyma and certain algae [ 1 , 2 , 3 ]. AST’s capacity to regulate inflammatory responses by preventing free radical formation and modulating redox balance has been described by a number of studies carried out in different species, mostly in vivo [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Thanks to these properties, AST finds applications in pharmaceutical, nutraceutical, and cosmetic industries, with various health benefits in humans [ 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%